Squalene attenuates the oxidative stress and activates AKT/mTOR pathway against cisplatin-induced kidney damage in mice - Sakul, Arzu; Ozansoy, Mehmet; Elibol, Birsen; Ayla, Sule; Gunal, Mehmet Yalcin; Yozgat, Yasemin; Kilic, Ulkan (Tubitak Scientific & Technological Research Council Turkey, 2019)
The clinical use of cisplatin, which is a first-line anticancer agent, is highly restricted due to its adverse effects on kidneys that lead to nephrotoxicity. Therefore, some potential reno-protective substances have been used in combination with cisplatin to cope with nephrotoxicity. Due to its high antitumor activity and oxygen-carrying capacity, we investigated the molecular effects of squalene against cisplatin-induced oxidative stress and kidney damage in mice. Single dose of cisplatin (7 mg/kg) was given to male Balb/c mice. Squalene (100 mg/kg/day) was administered orogastrically to mice for 10 days. Following sacrification, molecular alterations were investigated as analysis of the levels of oxidative stress index (OSI), inflammatory cytokines and cell survival-related proteins in addition to histopathological examinations in mice kidney tissue. The level OSI and Interferon-gamma (IFN-gamma) decreased in the cisplatin and squalene cotreated mice compared to cisplatin-treated mice. Squalene treatment also increased the activation of protein kinase B (AKT). Furthermore, cisplatin-induced inactivation of mammalian target of rapamycin (mTOR) and histopathological damages were reversed by squalene. It may be suggested that squalene ameliorated the cisplatin-induced histopathological damages in the kidney through activation of AKT/mTOR signaling pathway by regulating the balance of the redox system due to its antioxidative effect.
Keywords: AKT; cisplatin-induced nephrotoxicity; mice; mTOR; oxidative-stress; squalene